1965
DOI: 10.1007/bf00421485
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen-laden hepatomegaly in diabetes

Abstract: Summary.A 43-year old man is described who had been treated with insulin for diabetes for 18 years. For the last 3 years he had had nightly hypoglycaemie attacks. He was then found to have an enlarged liver, biopsy of which showed normal architecture but a markedly increased glycogen content. After his insulin was changed so that he no longer developed hypoglycaemia, his liver returned to normal size and normal glycogen content. Previous reports of glycogen-laden hepatomegaly are reviewed, and its mechanism is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1968
1968
1977
1977

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The similar rate of rise of the blood glucose in both diabetics and controls is to be expected if glucagon is stimulating the same hepatic processes. The enhanced peak and duration in diabetics may result from the diminished insulin response to glucagon and the increased levels of liver glycogen often present in treated diabetics (Middleton & Hockaday , 1965).…”
Section: Discussionmentioning
confidence: 99%
“…The similar rate of rise of the blood glucose in both diabetics and controls is to be expected if glucagon is stimulating the same hepatic processes. The enhanced peak and duration in diabetics may result from the diminished insulin response to glucagon and the increased levels of liver glycogen often present in treated diabetics (Middleton & Hockaday , 1965).…”
Section: Discussionmentioning
confidence: 99%
“…Divergent opinions have been expressed by Western workers with regard to these findings. Long (1947) believed that insulin, when given in physiologic amounts, inhibited liver glycogen deposition whereas Middleton and Hockaday (1965) observed increased glycogen storage in the liver leading to hepatomegaly if the disease was treated with insulin. Our observations in a few cases indicated that glycogen deposition either remained the same or was decreased to variable extent if the disease was kept adequately controlled for a year.…”
Section: Discussionmentioning
confidence: 99%